Renal Proximal Tubular Cells: A New Site for Targeted Delivery Therapy of Diabetic Kidney Disease - Hao Li; Wenni Dai; Zhiwen Liu; Liyu He (MDPI AG, 2022)
Diabetic kidney disease (DKD) is a major complication of diabetes mellitus (DM) and the leading cause of end-stage kidney disease (ESKD) worldwide. A significant number of drugs have been clinically investigated for the treatment of DKD. However, a large proportion of patients still develop end-stage kidney disease unstoppably. As a result, new effective therapies are urgently needed to slow down the progression of DKD. Recently, there is increasing evidence that targeted drug delivery strategies such as large molecule carriers, small molecule prodrugs, and nanoparticles can improve drug efficacy and reduce adverse side effects. There is no doubt that targeted drug delivery strategies have epoch-making significance and great application prospects for the treatment of DKD. In addition, the proximal tubule plays a very critical role in the progression of DKD. Consequently, the purpose of this paper is to summarize the current understanding of proximal tubule cell-targeted therapy, screen for optimal targeting strategies, and find new therapeutic approaches for the treatment of DKD.